Molecular Modeling Applied to the Discovery of New Lead Compounds for P2 Receptors Based on Natural Sources - Alberto, Anael Viana Pinto; da Silva Ferreira, Natiele Carla; Soares, Rafael Ferreira; Alves, Luiz Anastacio (Frontiers in Pharmacology, 2020)
P2 receptors are a family of transmembrane receptors activated by nucleotides and nucleosides. Two families have been described in mammals, P2X and P2Y. P2X receptors are ionotropic receptors activated mainly by ATP, while P2Y are metabotropic receptors activated by adenine and uracil nucleotides. The P2X family comprises seven members, P2X1 to P2X7, while P2Y consists of eight members P2Y1, P2Y2, P2Y4, P2Y6, P2Y11, P2Y12, P2Y13 and P2Y14. Both families are implicated in various diseases, such as inflammation, pain and CNS disorders, which makes them promising targets for the treatment of these conditions. Currently, only two drugs in the market act on P2 receptors, the antiplatelet medicine clopidogrel, prasugrel, and others acting via P2Y12, and diquafosol licensed only in Japan and South Korea. Alternatively, natural products have emerged as an extraordinary source of drugs that could be useful in clinical therapy to treat neurodegenerative, cardiac, metabolic, infectious and inflammatory diseases through P2 receptors. In drug discovery research, high throughput screening (HTS) techniques are employed by industries even with the disadvantages of being time-consuming and leading to high consumable expenses. In this scenario, the in silico virtual screening (VS) of biomolecules presents many advantages, allowing for the evaluation of thousands of molecules against a target, usually proteins, faster and cheaper than classical HTS. Additionally, new approaches allow for more information on the selected hits, such as absorption, distribution, metabolism, and toxicity, as well as predictions on biological activity and the lead likeness molecule. Then, selected biomolecules may be tested by molecular dynamics and, if necessary, rationally designed or modified for the target. The algorithms of these in silico tools are being improved to permit the precision development of new drugs and, in the future, this process will take the front of drug development against some CNS disorders. Therefore, this review discusses the methodologies of in silico tools concerning P2 receptors, as well as future perspectives and discoveries, such as the employment of artificial intelligence in drug discovery.